If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14=-3p+13+4p
We move all terms to the left:
-14-(-3p+13+4p)=0
We add all the numbers together, and all the variables
-(p+13)-14=0
We get rid of parentheses
-p-13-14=0
We add all the numbers together, and all the variables
-1p-27=0
We move all terms containing p to the left, all other terms to the right
-p=27
p=27/-1
p=-27
| x/7.7=-3 | | 8n+4=-4(2n-1) | | -3=-7p-7+8p | | 8=3(b-8)-(-2) | | 3m+5=2(m+2) | | -8+11d=9 | | 3(b+2)+6=18 | | 2=2(n-10) | | -2(-6+6b)=84 | | (3/4)x+5=(1/20x+9 | | f(-2)=2+3 | | 12-8z=148 | | 15=3(v=8) | | 8×2n=16 | | -(y-4)=0 | | 156=6(4v-2) | | 8×2^n=16 | | 1=m-8÷2 | | f(-2)=-2 | | 0=z-10÷-1 | | -248=-8n-4 | | 5(u-2)=-3u+30 | | 38=4(v+8)-7v | | 3000-5x=200 | | 4.8=60/r | | 54+9q=0 | | 28=4(v+8)-7v | | -4(h+-3)=16 | | 1(-5y+4)=19y= | | -22=x+3-6 | | –4(h+–3)=16 | | -2(m-9)=6 |